Disinfection and hand hygiene knowledge, attitude, and practices among childcare facilities staff during the COVID-19 pandemic in Anhui, China: a cross-sectional study - Chen, Fang; Xu, Qing Hua (Frontiers in Public Health, 2024)
Objective This study aimed to investigate the knowledge, attitude, and practice (KAP) regarding disinfection and hand hygiene, along with associated influencing factors among childcare facilities staff during the COVID-19 pandemic in Anhui, and to provide information for developing disinfection and hand hygiene strategies for childcare facilities. Methods A web-based cross-sectional study was conducted among Anhui Province residents in China in September 2020. In this study, 60 childcare facilities in two cities of Anhui Province were selected using the convenient sampling method for questionnaires. The questionnaires were distributed through a web-based platform. The disinfection and hand hygiene KAP scores among childcare facilities staff were calculated, and their influencing factors were analyzed. The accuracy rates of knowledge, attitude, and practice of behavior were calculated and analyzed. Results A total of 1,029 participants were included in the study. The disinfection and hand hygiene knowledge, attitude and practice ranged from approximately 5 to 23, 1 to 5, 3 to 13, respectively. The score of urban areas was higher than that of rural areas. Higher education levels and more years of working were associated with higher scores. Additionally, staff who received training or supervision had higher scores than those without. The categories with the lowest knowledge accuracy rate (46.3%), lowest attitude accuracy rate (4.2%), and “always” practice rate (5.3%) among childcare facility staff were all related to the question categories concerning the appropriate range of disinfectants for use. The accuracy rates of hand hygiene knowledge and attitude among the childcare facility staff were high (83.7%-99.6%), but the “always” practice rate was in the middle range (63.0%). Conclusion The disinfection and hand hygiene knowledge among childcare facilities staff was inadequate during the COVID-19 pandemic in Anhui. Continuous implementation of education and training, particularly in rural areas, is essential. Establishing a monitoring system to assess usage effectiveness and adverse reactions in China is critical. Interventions should focus on increasing compliance with hand hygiene practices. Further research should explore the training and intervention of disinfection and hand hygiene, the safety of disinfection measures, and more operational hand hygiene methods in childcare facilities.